Atuação do profissional de psicologia nos centros de referência especializados em assistência social - Freire, Mayara Limeira (2012)
This dissertation aims at analyzing how the performance of psychologists is in fighting sexual violence against children and adolescents in the Centres of Expertise on Social Welfare – Centros Especializados em Assistência Social (CREAS) - in the regional state of Paraiba. Thus, it was used the theoretical framework, expressed in the following categories: consciousness, subjectivity and mediation, ranging from the historicalcultural perspective, the concept of public policy, understood by the elementary structures of a policy, and benchmarks on the performance of the psychologist, his social commitment and the new playing field in public policy. As for the methodological approach, the field research took place in the state of Paraiba. The study included 11 psychologists, aged 25-65 years. Semi-structured interviews were used as tools and, for further analysis, the Alceste software. This program allows, from a quantitative analysis of the verbal elements of the interviews, for the understanding of the most significant words in the corpus, by lexical analysis, through the radical words, within the context in which they appear in the speech. Thus, eight blocks of analysis were obtained, which were prepared by Descending Hierarchical Classification Dendograms, creating classes that represent world views of the interviewees. The obtained results showed that the performance of psychologists in confronting sexual violence, with respect to activities developed for the protection and restoration of children’s and adolescents’ rights, is impaired due to: uncertainty, before the phenomenon of sexual violence, due to its complexity and lack of specific training for working with violence, and child and adolescent; insecurity evidenced by in-service impermanence, lack of coordination with the safety net, and a lack of adequate organizational support so that professionals can exercise their role in CREAS. From this, we understand that the difficulties experienced by psychologists regarding their role in comfronting sexual violence against children and adolescents, are consequences of various aspects which permeate both the accountability of the state, the viability of such means as physical support and organizational resources and specialized training to the public policy field, aimed at fighting sexual violence against children and adolescents, as the responsibility of each actor involved in the process, working in an active, political and committed way to the social and subjective aspects of violence, built and sociohistorically produced.